2016
DOI: 10.1590/0100-67622016000300018
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks as a New Tool for Assessing and Monitoring Wood Moisture Content

Abstract: -Drying of wood is necessary for its use and moisture control is important during this process. The aim of this study was to use artificial neural networks to evaluate and monitor the wood moisture content during drying. Wood samples of 2 × 2 × 4 cm were taken at 1.3 m above the ground, outside of radial direction, from seven 2-year-old materials and three 7-year-old materials. These samples were saturated and drying was evaluated until the equilibrium moisture content, then, the artificial neural networks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Some studies have developed ANN models to estimate wood density, 35,36 wood stiffness, 37 and wood strength, 38 as well as to assess the surface quality of wood 39 and to predict the moisture content of wood during drying. 40,41 With respect to the application of the ANN approach in classifications, most studies have shown promising findings as well as ours. For instance, Cui et al 26 have used laser-induced breakdown spectroscopy (LIBS) combined with ANN to classify four wood species and reported a correct specimen classification rate of 100% in the test set, using a model with a multilayer perceptron network and the Broyden−Fletcher− Goldfarb−Shanno iterative algorithm.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Some studies have developed ANN models to estimate wood density, 35,36 wood stiffness, 37 and wood strength, 38 as well as to assess the surface quality of wood 39 and to predict the moisture content of wood during drying. 40,41 With respect to the application of the ANN approach in classifications, most studies have shown promising findings as well as ours. For instance, Cui et al 26 have used laser-induced breakdown spectroscopy (LIBS) combined with ANN to classify four wood species and reported a correct specimen classification rate of 100% in the test set, using a model with a multilayer perceptron network and the Broyden−Fletcher− Goldfarb−Shanno iterative algorithm.…”
Section: Resultssupporting
confidence: 68%
“…ANN has been applied as a modeling tool to overcome various challenges in many timber forestry sectors. Some studies have developed ANN models to estimate wood density, , wood stiffness, and wood strength, as well as to assess the surface quality of wood and to predict the moisture content of wood during drying. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As alternative to traditional regression modeling, Artificial Neural Networks (ANNs) are composed of a massive parallel system integrated of simple processing units (artificial neurons), which calculate certain mathematical functions and allow to generalize assimilated knowledge to unknown data (Gorgens et al, 2009;Binoti, 2010;Binoti et al, 2015;Zanuncio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%